Fetal ani neonatal diagnosis of malformations in the urinary tract.: Experience and treatment in 30 cases - Pereyra Bonasso, J (Cirugía del Uruguay, 1987)
46 malformations of the urinary system are analyzed observed in 30 neonates. The diagnosis was made in the fetal period in 15 of them and in the neonatal period in the other 15.